Fibroblasts and monocyte macrophages contract and degrade three-dimensional collagen gels in extended co-culture - Zhu, Yunkui (BioMed Central, 2001)
BACKGROUND: Inflammatory cells are believed to play a prominent role during tissue repair and remodeling. Since repair processes develop and mature over extended time frames, the present study was designed to evaluate the effect of monocytes and fibroblasts in prolonged culture in three-dimensional collagen gels. METHODS: Blood monocytes from healthy donors and human fetal lung fibroblasts were cast into type I collagen gels and maintained in floating cultures for three weeks. RESULTS: Fibroblast-mediated gel contraction was initially inhibited by the presence of monocytes (P < 0.01). However, with extended co-culture, contraction of the collagen gels was greatly augmented (P < 0.01). In addition, with extended co-culture, degradation of collagen in the gels occurred. The addition of neutrophil elastase to the medium augmented both contraction and degradation (P < 0.01). Prostaglandin E(2) production was significantly increased by co-culture and its presence attenuated collagen degradation. CONCLUSION: The current study, therefore, demonstrates that interaction between monocytes and fibroblasts can contract and degrade extracellular matrix in extended culture.